2010
DOI: 10.1007/s11069-010-9523-8
|View full text |Cite
|
Sign up to set email alerts
|

Land–ocean tectonics (LOTs) and the associated seismic hazard over the Eastern Continental Margin of India (ECMI)

Abstract: The South Indian (Peninsular) Shield which includes both the Eastern and Western Continental Margins of India is not as stable as it was originally thought of. The importance of intraplate seismicity within this Shield has recently been realized with some devastating earthquakes that occurred during the last few decades. It is also significant to note that most of the Precambrian tectonic lineaments in this Shield are oriented in either a NW-SE or W-E direction, joining the eastern offshore. In contrast, the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…2), the Eastern Ghat Mobile Belt (EGMB), major shear zones and the rocks belonging to the Southern Granulite Terrain (SGT) at the Indian shield margin, have close linkages with a similar geology along East Antarctica (Yoshida et al 1999). Geophysical studies (Venkatarengan and Ray 1993;Subrahmanyam et al 1995Subrahmanyam et al , 2008Bastia et al 2010;Murthy et al 2010) at the coast revealed the extension of major Precambrian structural trends, basin scale faults/fractures into the offshore areas (Fig. 2).…”
Section: Regional Geotectonic History Of the Bobmentioning
confidence: 92%
See 1 more Smart Citation
“…2), the Eastern Ghat Mobile Belt (EGMB), major shear zones and the rocks belonging to the Southern Granulite Terrain (SGT) at the Indian shield margin, have close linkages with a similar geology along East Antarctica (Yoshida et al 1999). Geophysical studies (Venkatarengan and Ray 1993;Subrahmanyam et al 1995Subrahmanyam et al , 2008Bastia et al 2010;Murthy et al 2010) at the coast revealed the extension of major Precambrian structural trends, basin scale faults/fractures into the offshore areas (Fig. 2).…”
Section: Regional Geotectonic History Of the Bobmentioning
confidence: 92%
“…Details of the focal mechanisms are given in Table 1. Blue dots represent the location of micro-tremors in the coastal areas (Murthy et al 2010). Dashed lines across the east coast of India indicate the lineaments extending from onshore to offshore (after Murthy et al 2010).…”
Section: Regional Geotectonic History Of the Bobmentioning
confidence: 99%
“…10 The Luni River downstream of Tilwara, east of Barmer, Rajasthan. The Luni (meaning salty) is the only well integrated river system in the Thar Desert breakup resulted in the eastward tilt of the Peninsula and establishment of the easterly drainage (Murthy et al 2010). During its northward journey the western continental passive margin of India was impacted by two major hotspots (Marion and Réunion) and has experienced two episodes of separation-Madagascar-Greater India *80-90 Ma and Seychelles-India *65 Ma (Norton and Sclater 1979;Storey et al 1995).…”
Section: Pre-cenozoic Geology and Geomorphologymentioning
confidence: 99%
“…The basin is dominated by deltaic plains near the sea-land boundary. From the study of gravity anomalies, three basins have been characterized separated by the two basement horsts namely, Bapatla and Tanuku (Venkatarangan and Ray 1993;Murthy et al 1995;Subrahmanyam et al 2008;Murthy et al 2010). The basin has significant hydrocarbon potential both in the Tertiary delta as well as in the channel-levee-overbank play types in the deepwaters (Saxena et al 2011).…”
Section: Introductionmentioning
confidence: 99%